An Adaptive H∞-Based Formation Control for Multirobot Systems. (7th June 2012) - Shabani, Faridoon; Ranjbar, Bijan; Ghadamyari, Ali
Abstract : We describe a decentralized formation problem for multiple robots, where an H ∞ formation controller is proposed. The network of dynamic agents with external disturbances and uncertainties are discussed in formation problems. We first describe how to design social potential fields to obtain a formation with the shape of a polygon. Then, we provide a formal proof of the asymptotic stability of the system, based on the definition of a proper Lyapunov function and H ∞ technique. The advantages of the proposed controller can be listed as robustness to input nonlinearity, external disturbances, and model uncertainties, while applicability on a group of any autonomous systems with n -degrees of freedom. Finally, simulation results are demonstrated for a multiagent formation problem of a group of six robots, illustrating the effective attenuation of approximation error and external disturbances, even in the case of agent failure or leader tracking.